AB0140 Lupus-prone slam haplotype exerts monocytosis and develops specific phenotype of autoimmune disease introduced by yaa mutation. (15th June 2017) - Amano, H; Nishikawa, K; Lin, Q; Kawano, S; Yamaji, K; Hirose, S; Tamura, N
Abstract : Background: We previously obtained a 129-derive FcγRIIB-deficient C57BL/6 (B6) congenic strain of mice, which spontaneously developed severe rheumatoid arthritis (RA) 1 . The introduction of the Yaa (Y-linked autoimmune acceleration) mutation, which is a consequence of a translocation from the telomeric end of the X chromosome containing the Tlr7 gene onto the Y chromosome, to the FcγRIIB-deficient B6 mice (B6.FcγRIIB-/-. Yaa ) developed lupus like nephritis but not RA 2 . Objectives: By extensively backcrossing 129-based FcγRIIB-deficient mice to B6 mice, we established wildtype FcγRIIB and 129-derive autoimmune-prone SLAM haplotype ( Slam 129 ). We examined the phenotype of Slam 129 mice, and also Slam 129 . Yaa mice by introducing Yaa mutation to these mice. Methods: We analyzed peripheral blood monocyte subset and also serum autoantibodies as well as immunohistopathological findings of kidneys and lungs. Results: Slam 129 mice showed age-associated monocytosis with marked expansion of Gr-1 negative monocytes, also perivascular inflammatory cell infiltration in lungs. But they did not show any pathogenic autoantibodies. When introducing Yaa mutation, Slam 129 . Yaa mice showed significant increase the serum levels of anti-RNP antibodies and anti-Sm antibodies. Although they showed significant increase of serum levels of IgM class anti-dsDNA antibodies, they did not show the elevation of IgG class anti-dsDNA antibodies. Also they developed nephritis but the pathological score was significantly lower than B6.FcγRIIB-/-. Yaa mice. Conclusions: Autoimmune-prone SLAM haplotype plays a role for Gr-1 negative monocytosis and Slam 129 . Yaa mice developed specific lupus phenotype with elevation of anti-RNP and anti-Sm autoantibodies. References: Sato-Hayashizaki A, Ohtsuji M, Lin Q, Hou R, Ohtsuji N, Nishikawa K, Tsurui H, Sudo K, Ono M, Izui S, Shirai T, Takai T, Nishimura H, Hirose S. Presumptive role of 129 strain-derived Sle16 locus in rheumatoid arthritis in a new mouse model with Fcγ receptor type IIb-deficient C57BL/6 genetic background. Arthritis Rheum. 63(10):2930–8, 2011. Kawano S, Lin Q, Amano H, Kaneko T, Nishikawa K, Tsurui H, Tada N, Nishimura H, Takai T, Shirai T, Takasaki Y, Hirose S. Phenotype conversion from rheumatoid arthritis to systemic lupus erythematosus by introduction of Yaa mutation into FcγRIIB-de ficient C57BL/6 mice. Eur J Immunol. 43:1–9, 2013. Disclosure of Interest: None declared